Preventing and improving interactions between autistic individuals and the criminal justice system: A roadmap for research. Issue 10 (17th August 2021) - Shea, Lindsay Lawer; Cooper, Dylan; Wilson, Amy Blank
Abstract: Researchers have identified that autistic individuals are encountering the criminal justice system as victims, offenders, and witnesses at high rates. The prevalence of autism spectrum disorder (ASD) is increasing and generating a comprehensive approach to addressing criminal justice system involvement among autistic individuals is a timely and urgent need. Revisions to an established framework generated for use among individuals with mental health diagnoses, the sequential Intercept Model (SIM), were produced by an international consortium of interdisciplinary stakeholders presenting a new opportunity to identify gaps in ASD research and generate preventive solutions across the criminal justice system. The revised SIM maps each criminal justice system component, or Intercept, and includes paths for the experiences of autistic individuals as victims or witnesses to crimes as well as offenders to catalyze new and interdisciplinary research, policy, and practice efforts. As the field of ASD research continues to grow, the revised SIM is a promising pathway to avoiding siloed research approaches, including diverse autistic voices, and contributing to international dialogue about criminal justice reform at a critical juncture. Lay Summary: Autistic individuals are encountering the criminal justice system as victims, offenders, and witnesses at high rates. A revised version of the SIM generated by an international consortium provides a cohesive framework to ensure research focused on this topic extends across the criminal justice system. Preventing and improving interactions between autistic individuals and the criminal justice system is an urgent research, policy, and practice need.